Nền đệ nhị Việt Nam Cộng Hòa và sự sụp đổ của nó (1965 - 1975) - Nguyễn Thị Qúy (Đại học Sư phạm, Đại học Đà Nẵng, 2012)
Nền đệ nhị Việt Nam Cộng hòa (1965 -1975). Sự sụp đổ của nền đệ nhị Việt Nam Cộng hòa